Mengungkap Algorithmic Pricing Cartel dalam E-Commerce melalui Leniency Program - Auliansyah Pratama, Reiyan; Rahmadani, Nindy (Komisi Pengawas Persaingan Usaha, 2025)
The development of the digital economy has created a new form of cartel practice, where business actors use pricing algorithms to coordinate automatic price setting on e-commerce platforms, known as the Algorithmic Pricing Cartel. This phenomenon poses a challenge for competition law enforcement, as collusion occurs through algorithmic systems that are difficult to detect. The purpose of this study is to analyze the role and mechanism of pricing algorithms in facilitating digital cartels, the urgency of regulating a leniency program in Indonesia, and a comparison with the United States, the European Union, and Japan. The research method used is a literature study with a normative and comparative approach to relevant regulations and competition policies. The findings indicate that pricing algorithms can facilitate price fixing. Hypothetically, implementing a leniency program in Indonesia could serve as a strategic solution to uncover and address pricing algorithms cartels and strengthen competition law enforcement in the digital economy era.